2015
DOI: 10.1111/aje.12245
|View full text |Cite
|
Sign up to set email alerts
|

A study on the postrelease behaviour and habitat preferences of black rhinos (Diceros bicornis) reintroduced into a fenced reserve in Namibia

Abstract: Translocations and reintroductions are key elements for the population management of the critically endangered black rhino (Diceros bicornis, Linnaeus, 1758). In this study, we investigated the postrelease behaviour and habitat preferences of a black rhino starter group (n = 4) on the individual level. The animals were reintroduced to a fenced game reserve (87 km2) in North-Central Namibia 1 year prior to our study. We used camera traps and very high frequency (VHF) radiotelemetry to examine the animals' tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Males, on the contrary, might have explored more possible territories or have dispersed away from previously released individuals (Linklater & Swaisgood, 2008). These findings are similar to previous studies, where males showed slightly larger home ranges after translocations, but overall, no significant differences in home ranges sizes between sexes were found (Göttert et al, 2010; Schwabe et al, 2015; Tatman et al, 2000). Our results for the effect of age are different to a study by Göttert et al (2010), who observed more exploratory behaviour in adults than subadults.…”
Section: Discussionsupporting
confidence: 92%
“…Males, on the contrary, might have explored more possible territories or have dispersed away from previously released individuals (Linklater & Swaisgood, 2008). These findings are similar to previous studies, where males showed slightly larger home ranges after translocations, but overall, no significant differences in home ranges sizes between sexes were found (Göttert et al, 2010; Schwabe et al, 2015; Tatman et al, 2000). Our results for the effect of age are different to a study by Göttert et al (2010), who observed more exploratory behaviour in adults than subadults.…”
Section: Discussionsupporting
confidence: 92%
“…The region's economy is dominated by tourism and hunting enterprises, sedentary livestock production at low stocking rates, and seminomadic pastoralism (Mendelsohn 2006). The area supports a variety of arid savanna and desert-adapted mammalian species, including African elephant (Loxodonta africana) and black rhinoceros (Diceros bicornis; Schwabe et al 2015). Predators include lion (Panthera leo), leopard (P. pardus), cheetah (Acinonyx jubatus), spotted hyena (Crocuta crocuta), and brown hyena (Hyaena brunnea; Lindsey et al 2013, Trinkel et al 2017.…”
Section: Study Areamentioning
confidence: 99%
“…Black rhinos are largely solitary and sedentary but possess home ranges that overlap intersexually ( 19 , 24 , 29 , 30 ), making home-range connectivity critical for maintaining social interactions ( 29 , 31 , 32 ). Particularly for a nongregarious species, communication through scent is important and thus overlap in territories is essential.…”
Section: Resultsmentioning
confidence: 99%